2017
DOI: 10.1016/j.cobme.2017.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Novel biomaterials to study neural stem cell mechanobiology and improve cell-replacement therapies

Abstract: Neural stem cells (NSCs) are a valuable cell source for tissue engineering, regenerative medicine, disease modeling, and drug screening applications. Analogous to other stem cells, NSCs are tightly regulated by their microenvironmental niche, and prior work utilizing NSCs as a model system with engineered biomaterials has offered valuable insights into how biophysical inputs can regulate stem cell proliferation, differentiation, and maturation. In this review, we highlight recent exciting studies with innovati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 81 publications
0
12
0
Order By: Relevance
“…Physical characteristics of the engineered environments include stiffness, morphology, and elasticity. Chemical characteristics include hydrophilicity and hydrophobicity and involve chemical moieties that may significantly affect cellular pathways and processes [12,13]. Various materials of different forms and chemical compositions, including polymer/inorganic thin films, composite scaffolds, hydrogels, and fibrous scaffolds, have been constructed as cell culture substrates to control mammalian cells.…”
Section: Engineered Materialsmentioning
confidence: 99%
“…Physical characteristics of the engineered environments include stiffness, morphology, and elasticity. Chemical characteristics include hydrophilicity and hydrophobicity and involve chemical moieties that may significantly affect cellular pathways and processes [12,13]. Various materials of different forms and chemical compositions, including polymer/inorganic thin films, composite scaffolds, hydrogels, and fibrous scaffolds, have been constructed as cell culture substrates to control mammalian cells.…”
Section: Engineered Materialsmentioning
confidence: 99%
“…By studying the biomaterials composition influence on stem cell transplantation therapy, it has been observed that material stiffness confers stem cells’ different properties. Stiffer substrates direct NSCs to astrocyte differentiation, while softer substrates lead NSCs to neurogenic differentiation [ 191 , 192 ]. Chemical composition proves essential for potential beneficial outcomes, particularly in injectable hydrogels development [ 192 ].…”
Section: Remodeling Of the Stroke Tissue Microenvironment Within The Brainmentioning
confidence: 99%
“…160 For example, various studies have demonstrated that softer substrates can promote neurogenic differentiation in NSCs, while stiffer substrates will instead direct them towards astrocyte differentiation. 161 This highlights the need to optimize these biomaterials for stem cell viability, differentiation, and proliferation. A recent meta-analysis found that biomaterialbased interventions have led to lesion volume reduction and improved neurological outcomes in stroke rodent models.…”
Section: Biomaterialsmentioning
confidence: 99%
“…Additionally, these scaffolds may intrinsically contain properties that can provide cues to stem cells such as matrix topology, mechanical forces, and biochemical properties [ 160 ]. For example, various studies have demonstrated that softer substrates can promote neurogenic differentiation in NSCs, while stiffer substrates will instead direct them towards astrocyte differentiation [ 161 ]. This highlights the need to optimize these biomaterials for stem cell viability, differentiation, and proliferation.…”
Section: Improvement Of Stem Cell Application In Ischemic Brain Injurmentioning
confidence: 99%